The interrelationship between spatial organization, social interaction and landscape setting of the homestay towards Islamic built environment - Othman, Rashidi (2018)
With the emergence of the homestay programme, Malaysia as a multi-racial country offers a golden opportunity for a tourist to experience different cultures from different races. However, the homestay programme offered does not readily implement the Shariah Compliant and thus minimally translate to the Islamic way of life as Muslim country which should be portrayed to international guests as part of their travel experience. Most of the homestay offer the guest to stay with the host’s family members without determining the space limitation within the house between the guest and host. Therefore, this research explores the complication that exists in Muslim homestay. The issue about the spatial organization, space limitation, social interaction (ikhtilat) and landscape setting of the homestay will be identified and solved by implementing Shariah compliant principles. The selected homestay can be categorized as moderate in practicing the Shariah-compliant. In conclusion, the homestay providers are encouraged to apply and practice a Muslim-friendly and Shariah Compliant homestay system for guests.